Intermittent Occlusion of the Superior Vena Cava to Improve Hemodynamics in Patients With Acutely Decompensated Heart Failure: The VENUS-HF Early Feasibility Study. (February 2022) - Kapur, Navin K.; Kiernan, Michael S.; Gorgoshvili, Irakli; Yousefzai, Rayan; Vorovich, Esther E.; Tedford, Ryan J.; Sauer, Andrew J.; Abraham, Jacob; Resor, Charles D.; Kimmelstiel, Carey D.; Benzuly, Keith H.; Steinberg, Daniel H.; et al.
Abstract : Background: Reducing congestion remains a primary target of therapy for acutely decompensated heart failure. The VENUS-HF EFS (VENUS-Heart Failure Early Feasibility Study) is the first clinical trial testing intermittent occlusion of the superior vena cava with the preCARDIA system, a catheter mounted balloon and pump console, to improve decongestion in acutely decompensated heart failure. Methods: In a multicenter, prospective, single-arm exploratory safety and feasibility trial, 30 patients with acutely decompensated heart failure were assigned to preCARDIA therapy for 12 or 24 hours. The primary safety outcome was a composite of major adverse cardiovascular and cerebrovascular events through 30 days. Secondary end points included technical success defined as successful preCARDIA placement, treatment, and removal and reduction in right atrial and pulmonary capillary wedge pressure. Other efficacy measures included urine output and patient-reported symptoms. Results: Thirty patients were enrolled and assigned to receive the preCARDIA system. Freedom from device- or procedure-related major adverse events was observed in 100% (n=30/30) of patients. The system was successfully placed, activated and removed after 12 (n=6) or 24 hours (n=23) in 97% (n=29/30) of patients. Compared with baseline values, right atrial pressure decreased by 34% (17±4 versus 11±5 mm Hg, P <0.001) and pulmonary capillary wedge pressure decreased by 27% (31±8 versus 22±9 mm Hg, P <0.001). Compared with pretreatment values, urine output and net fluid balance increased by 130% and 156%, respectively, with up to 24 hours of treatment ( P <0.01). Conclusions: We report the first-in-human experience of intermittent superior vena cava occlusion using the preCARDIA system to reduce congestion in acutely decompensated heart failure. PreCARDIA treatment for up to 24 hours was well tolerated without device- or procedure-related serious or major adverse events and associated with reduced filling pressures and increased urine output. These results support future studies characterizing the clinical utility of the preCARDIA system. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03836079. Abstract : Supplemental Digital Content is available in the text.